Proposed new definition for hospital-acquired SARS-CoV-2 infections: results of a confirmatory factor analysis - Nicolás Reinoso Schiller; Claas Baier; Isabella Dresselhaus; Ulrike Loderstädt; Dirk Schlüter; Tim Eckmanns; Simone Scheithauer (Cambridge University Press, 2024)
Abstract Objective: The present study aims to develop and discuss an extension of hospital-acquired severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infections (HA-SIs) definition which goes beyond the use of time parameters alone. Design: A confirmatory factor analysis was carried out to test a suitable definition for HA-SI. Setting and Patients: A two-center cohort study was carried out at two tertiary public hospitals in the German state of lower Saxony. The study involved a population of 366 laboratory-confirmed SARS-CoV-2-infected inpatients enrolled between March 2020 and August 2023. Results: The proposed model shows adequate fit indices (CFI.scaled = 0.959, RMSEA = 0.049). A descriptive comparison with existing classifications revealed strong features of our model, particularly its adaptability to specific regional outbreaks. Conclusion: The use of the regional incidence as a proxy variable to better define HA-SI cases represents a pragmatic and novel approach. The model aligns well with the latest scientific results in the literature. This work successfully unifies, within a single model, variables which the recent literature described as significant for the onset of HA-SI. Further potential improvements and adaptations of the model and its applications, such as automating the categorization process (in terms of hospital acquisition) or employing a comparable model for hospital-acquired influenza classification, are subjects open for discussion.